2004
DOI: 10.1158/0008-5472.can-04-1702
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Carcinogenesis Rat Model of Ovarian Preneoplasia and Neoplasia

Abstract: Animal models of ovarian cancer are crucial for understanding the pathogenesis of the disease and for testing new treatment strategies. A model of ovarian carcinogenesis in the rat was modified and improved to yield ovarian preneoplastic and neoplastic lesions that pathogenetically resemble human ovarian cancer. A significantly lower dose (2 to 5 g per ovary) of 7,12-dimethylbenz(a)anthracene (DMBA) was applied to the one ovary to maximally preserve its structural integrity. DMBA-induced mutagenesis was additi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 37 publications
2
66
0
7
Order By: Relevance
“…Furthermore, we also observed that the basal levels of the p53 protein were also increased in the MAD2DC-agar cells (Figure 5a). It is possible that DMBA treatment may have caused mutations on the p53 gene as previously reported (Stewart et al, 2004) which leads to stabilization of this protein. However, sequencing analysis of the p53 gene showed no evidence of mutation, suggesting that the increased p53 expression is not the result of DMBA-induced mutation.…”
Section: Mad2dc Promotes Carcinogen-induced Transformationmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, we also observed that the basal levels of the p53 protein were also increased in the MAD2DC-agar cells (Figure 5a). It is possible that DMBA treatment may have caused mutations on the p53 gene as previously reported (Stewart et al, 2004) which leads to stabilization of this protein. However, sequencing analysis of the p53 gene showed no evidence of mutation, suggesting that the increased p53 expression is not the result of DMBA-induced mutation.…”
Section: Mad2dc Promotes Carcinogen-induced Transformationmentioning
confidence: 78%
“…For example, der(1)t(1;16) was observed in over 87% of the MAD2DC-agar cells while this aberration was not detected in the MAD2DC cells (see white circles in Figure 2a). Since the carcinogenic effect of DMBA is believed to be through its mutagenic effect on the genome (Stewart et al, 2004), it is not a surprise to observe the increased chromosomal structural alterations in the MAD2DC-agar cells. Cell cycle analysis revealed a similar pattern between MAD2DC and MAD2DC-agar cells before and after exposure to nocodazole (Figure 3a) and suggested that the polyploidy MAD2DC-agar cells were also able to undergo cell division in the presence on microtubule disruption.…”
Section: Mad2dc Promotes Carcinogen-induced Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct application of DMBA to the ovary has been shown to result in selective development of ovarian malignancies in both rats and mice. 2,[6][7][8][9][10] The development of a post-menopausal animal model for ovarian cancer may prove useful in evaluating diagnostic tools to aid in differentiating benign and malignant ovarian pathology and provide better understanding of features characteristic of early cancers to improve their detection. Optical coherence tomography is an emerging, non-destructive imaging modality using near-infrared light to create cross-sectional images of tissue structure with near histological resolution (2-20 µm) with the advantage of up to 2 mm penetration depth compared to other optical technologies which may only have 100 micron or less penetration.…”
Section: Resultsmentioning
confidence: 99%
“…O gene ras, quando alterado (oncogen ras), o que ocorre em cerca de 10% a 20% dos tumores de mama (Stewart et al, 2004;De Vita et al, 2004) Rogers et al (1998) e Russo et al (1990Russo et al ( , 2005a.…”
Section: R Re Ev VI Is Sã ãO O D Da a L Li It Te Er Ra At Tu Ur Ra A unclassified